PERANCANGAN MUSEUM VAN DER PIJL DI BANJARBARU - Arifudin, Ahmad; Aufa, Naimatul (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
The City of Banjarbaru has one of the important figures in the process of regional development, namely Van der Pijl. He was a Dutch architect who designed a master plan of Banjarbaru city and several government buildings that until today were still in use. Van der Pijl role in the construction of Banjarbaru city is very important, but nowadays many people do not know the development of the city of Banjarbaru (early found) about the figure of Van der Pijl itself. So the need for a container to reintroduce and give an understanding of Van der Pijl in the process of building Banjarbaru city.